DAMPAK PENDEMI COVID-19 TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Dhea Maya Afifah; Eka Dian Lestari; Rafni Nadia Prianti (EJoES (Educational Journal of Elementary School), 2021)
This research was conducted with the aim of knowing the impact of covid-19 on learning in elementary schools. This type of research is qualitative with the method used is literature review. The results obtained from this study are divided into three types including things that are felt 1) students; 2) parents; and 3) teachers. The impact felt by students, namely the culture of distance learning affects the ability of students to absorb the material presented, this is because students are used to face-to-face learning, while the impact felt by parents is that there is an additional cost in supporting the effectiveness of their child's learning during the pandemic. namely the cost of purchasing a smartphone and internet package. The impact felt by the teacher is the ability to manage online learning including mastery of technology such as the application of social media used during learning. The conclusion of this study is the support and cooperation of parents for the success of learning is needed. Teacher and school communication with parents must be maintained smoothly